THE LINK BETWEEN COMPONENTS OF PERFORMANCE MANAGEMENT AND PERFORMANCE MANAGEMENT EFFECT - Challa Amdissa Jiru; Tilahun Teklu; Deribe Assefa Aga (Annals of the University of Craiova for Journalism, Communication and Management)
Research findings on the outcomes of performance management are inconclusive as researches reported both intended and unintended consequences of performance management. This paper investigates the extent to which the components of the performance management process influence the performance management effect in the public organizations. Performance management comprises a range of practices an organization engages in, from which this study investigates the influence of participation in target setting, performance information use, performance information processing capacity, performance review, performance indicators quality, and provision of performance management training on performance management effects. Understanding the link between components of performance management and performance management effects would guide how to improve performance management. Regression analysis based on data obtained from a survey of public sector organizations in Ethiopia indicates the influence of Participative target setting, Performance information processing capacity and Use of performance information on the Performance management effects were not statistically significant. In contrast, Performance indicators quality, Provision of training on performance management, and Performance Reviews significantly affect performance management outcomes. The study point outs the strategies the organizations can implement to improve the Performance management effects.